Perceptions of tax fairness and tax compliance behaviour: a comparative study - Natrah Saad, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This cross-cultural study compares the perceptions of tax fairness of New Zealand and Malaysian individual taxpayers of their respective national income tax systems and investigates the consequences of those taxpayers 'perceptions of tax fairness, as well as other important variables, on their compliance behaviour. The hypotheses of the study were tested using the responses to a questionnaire survey. A t-test and Partial Least Squares analyses were used to analyse the survey data. The results suggest that Malaysian taxpayers have significantly better perceptions of fairness of their income tax systems than their New Zealand counterparts. However, New Zealand taxpayers were found to be more compliant regarding their tax responsibility. The most important factor in explaining taxpayers 'compliance behaviour between the two countries was the attitude of individuals towards compliance, followed by subjective norms. Perceptions of tax fairness, which were highly influenced by both tax knowledge and the perceived complexity of the tax system, was influential in explaining tax compliance.